Facilitators and barriers to the self-management of COPD: a qualitative study from rural Nepal. Issue 3 (9th March 2020) - Yadav, Uday Narayan; Lloyd, Jane; Hosseinzadeh, Hassan; Baral, Kedar Prasad; Dahal, Sagar; Bhatta, Narendra; Harris, Mark Fort
Abstract : Objective: To understand the facilitators and barriers to the self-management of chronic obstructive pulmonary disease (COPD) in rural Nepal. Settings: Community and primary care centres in rural Nepal. Participants: A total of 14 participants (10 people with COPD and 4 health care providers) were interviewed. Primary and secondary outcome measure(s): People with COPD and healthcare provider's experience of COPD self-management in rural Nepal. Results: Facilitators and barriers affecting COPD self-management in Nepal operated at the patient-family, community and service provider levels. People with COPD were found to have a limited understanding of COPD and medications. Some participants reported receiving inadequate family support and described poor emotional health. At the community level, widespread use of complementary and alternative treatment was found to be driven by social networks and was used instead of western medicine. There were limited quality controls in place to monitor the safe use of alternative treatment. While a number of service level factors were identified by all participants, the pertinent concerns were the levels of trust and respect between doctors and their patients. Service level factors included patients' demands for doctor time and attention, limited confidence of people with COPD in communicating confidently and openly with their doctor, limited skills and expertise of the doctors in promoting behavioural change, frustration with doctors prescribing too many medicines and the length of time to diagnose the disease. These service level factors were underpinned by resource constraints operating in rural areas. These included inadequate infrastructure and resources, limited skills of primary level providers and lack of educational materials for COPD. Conclusions: The study findings suggest the need for a more integrated model of care with multiple strategies targeting all three levels in order to improve the self-management practices among people with COPD.